PRÁTICAS DE TURISMO DOS CLIENTES DE UMA AGÊNCIA DE VIAGENS EM NAVIRAÍ-MS - HELENA MAIA RIO (2023)
The paper aims to analyze the tourism practices of clients of a tourism agency in Naviraí-MS. Specifically, we presente the profile of the agency's clients, as well as travel data over a period of one year (May 2022 to May 2023). The literature review involved the themes: tourism and tourism consumer profile. We made a descriptive quantitative research, using documentary research. We use data from the company studied, considering reservations made from May 2022 to May 2023. The data was analyzed using descriptive statistics and presented in graphs and tables. As a result, we observed that the public is mostly made up of women aged between 24 and 33 years, businesswomen, private sector employees and independent professionals, with an average ticket per purchase of R$ 5,138.30. As for travel preference, there are national destinations, especially the Northeast region, in the cities of Porto Seguro and Porto de Galinhas. Regarding international destinations, the main one was Bariloche in Argentina. With these analyses, the agency can use the data to offer new products and services based on customer preferences.